Metagenomic-based characterization of the gut virome in patients with polycystic ovary syndrome - Huang, Liansha; Wu, Xiaoling; Guo, Shumin; Lv, Ying; Zhou, Peng; Huang, Guangrong; Duan, Zuzhen; Sun, Wen (Frontiers in Microbiology, 2022)
Background: Polycystic ovary syndrome (PCOS) is a complex disease that afflicts women of reproductive age, and its pathological mechanism has not been well explained. The gut microbiota is believed to be closely related to the development of PCOS. Although an important component of the gut microbiome, the role of the gut virome in the development of PCOS is still unclear. Methods: In this study, we profiled and compared the gut viral community of 50 patients with PCOS and 43 healthy women based on analysis of their fecal whole-metagenome dataset. Results: The gut virome of PCOS patients exhibited a significant decrease in within-sample viral diversity and a remarkable alteration of the overall virome composition compared with that of healthy controls. At the family level, Siphoviridae was significantly depleted in the gut virome of patients, while Quimbyviridae was enriched. We identified 1,089 viral operational taxonomic units (vOTUs) that differed in relative abundance between the two groups, of which 455 vOTUs were enriched in PCOS patients (including numerous Bacteroidaceae phages) and 634 were enriched in controls (including numerous viruses predicted to infect Oscillospiraceae, Prevotellaceae, and Ruminococcaceae). Functional comparison of the PCOS-enriched and control-enriched vOTUs uncovered the viral functional signatures associated with PCOS. Furthermore, we demonstrated gut viral signatures for disease discrimination and achieved an area under the receiver operator characteristic curve (AUC) of 0.938, demonstrating the potential of the gut virome in the prediction of PCOS. Conclusion: Our ﬁndings reveal speciﬁc alterations in viral diversity and taxonomic and functional compositions of the gut virome of PCOS patients. Further studies on the etiology of PCOS and the gut viral community will offer new prospects for treating and preventing PCOS and its related diseases.